Creative Aspects of Hafeez Taib’s Naat - Dr. Shagufta Firdous Dr. Muhammad Afzal Butt (دریافت, 2022)
Dr Shahida Sardar is a renowned poetess of Khyber Pakhtunkhwa. Hafeez Taib is renowned Naat writer. He has a unique natiya consciousness among modern poets. He described the Holy Prophet’s(S.A.W) love in various poetry genres like Ghazal , Free verse , sonnet Qatta, Rubai and special form of Alkosaria, . Which includes the ideal aspects of the Prophet's biography, contemporary issues, prayer style, Adorned with sincerity, devotion and the aspect of hope. In his naats, the problems of his time are also reflected, he not only influenced modern naat-writing at the intellectual level, but he also has many experiences.This article will present thematic dimensions   and creative aspects of his poetry.